Massive pulmonary tumor microembolism secondary to hepatic dearterialization due to embolization of a hepatocarcinoma - Bagnulo, Homero; Estefan, Alberto; Cereijo, Inés; Cotelo, Ana; Salice, Mario; Tiscornia, Eduardo; Gravina, Gustavo (Cirugía del Uruguay, 1979)
A 59 - year - old male patient develo"ped massive tumora microembolism secondary to hepatic dearterialization resulting from selective arterial embolization of a hepatocarcinoma. He entered the hospital as a result of pain in right hemi - thorax, hepatomegalia and general repercussion. Paraclinicar studies ( hepatic scintollography, arteriography, laparoscopy and biopsy) indicated a multinodular hepatocarcinoma. Hepatic dearterialization for antalgic purposes was decided. The procedure was followed by the clinical picture which is typical of multiple pulmonary embolism. Death occurred 30 hours after surgery. Post mortem showed a differentiated multinodular hepato'carcinoma, partially necrosed, which had developed in a cyrrhotic liver with intrasinusoidal hepatic metastasis. Multiple tumoral microembolism had occurred in both lungs, The cause of death was attributed to release of tumoral emboli originated in necrosis of neoplasic growths in the interior of suprahepatic veins. The paper contemplates the possibility that intrasinusoidal hepatic metastases are secondary to tumoral emboli released in the portal venous system; these might also condition a portal thrombosis. Study of this case leads to the conclusio'n that an exhaustive evaluation of the portal venous and suprahepatic systems should be performed in cases hepatic dearterialization due to hepatocarcinoma.